Czech-Scottish Cultural Standards at Work Environment - Valterová, Jana; Křečková Kroupová, Zuzana, 1972-; Bartošek, Josef; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
This diploma thesis is focused on Czech-Scottish cultural standards at work environment. The main aim is to define Scottish cultural standards at work environment from the Czech point of view and to compare them with the theory. The thesis begins with the definition of culture, cultural dimensions introduced by G. Hofstede, F. Trompenaars and E. T. Hall and cultural standards by A. Thomas. It continues to the description of Scotland with its geography, history, language, economic situation and various systems in the society, such as the legal system, educational system, health care system, a role of the family and religion. Further, Scottish national identity, key values and traditions are identified and there are added some information about work in Scotland. The thesis then leads us onwards to the determination of eight cultural standards at work environment and six cultural standards connected with the daily life in Scotland based on the qualitative research. The standards concerning work environment are further compared with the theory. At the end of the thesis, there are provided some recommendations for Czechs who are going to work with Scots.
Vedoucí práce: Zuzana Křečková Kroupová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses